Three-Color Chromosome Painting as Seen through the Eyes of mFISH: Another Look at Radiation-Induced Exchanges and Their Conversion to Whole-Genome Equivalency - Loucas, Bradford D.; Shuryak, Igor; Cornforth, Michael N. (Frontiers in Oncology, 2016)
Whole-chromosome painting (WCP) typically involves the fluorescent staining of a small number of chromosomes. Consequently, it is capable of detecting only a fraction of exchanges that occur among the full complement of chromosomes in a genome. Mathematical corrections are commonly applied to WCP data in order to extrapolate the frequency of exchanges occurring in the entire genome (whole genome equivalency; WGE). However, the reliability of WCP to WGE extrapolations depends on underlying assumptions whose conditions are seldom met in actual experimental situations, in particular the presumed absence of complex exchanges. Using mFISH, we analyzed the induction of simple exchanges produced by graded doses of 137Cs gamma rays (0-4 Gy), and also 1.1 GeV 56Fe ions (0-1.5 Gy). In order to represent cytogenetic damage as it would have appeared to the observer following standard 3-color WCP, all mFISH information pertaining to exchanges that did not specifically involve chromosomes 1, 2 or 4 was ignored. This allowed us to reconstruct dose responses for 3-color apparently simple (AS) exchanges. Using extrapolation methods similar to those derived elsewhere, these were expressed in terms of whole-genome equivalency for comparison to mFISH data. Based on AS events, the extrapolated frequencies systematically overestimated those actually observed by mFISH. For gamma rays these errors were practically independent of dose. When constrained to a relatively narrow range of doses, the WGE corrections applied to both 56Fe and gamma rays predicted genome-equivalent damage with a level of accuracy likely sufficient for most applications. However, the apparent accuracy associated with WCP to WGE corrections is both fortuitous and misleading. This is because (in normal practice) such corrections can only be applied to AS exchanges, which are known to include complex aberrations in the form of pseudosimple exchanges. When WCP to WGE corrections are applied to true simple exchanges (TR), the results are less than satisfactory, leading to extrapolated values that underestimate the true WGE response by unacceptably large margins. Likely explanations for these results are discussed, as well as their implications for radiation protection. Thus, in seeming contradiction to notion that complex aberrations be avoided altogether in WGE corrections and in